Dynamic color displays using stepwise csvity resonators - Chen, Yiqing; Duan, Xiaoyang; Matuschek, Marcus; Neubrech, Frank; Liu, Na (Nano letters, 2017)
High-resolution multicolor printing based on pixelated optical nanostructures is of great importance for promoting advances in color display science. So far, most of the work in this field has been focused on achieving static colors, limiting many potential applications. This inevitably calls for the development of dynamic color displays with advanced and innovative functionalities. In this Letter, we demonstrate a novel dynamic color printing scheme using magnesium-based pixelated Fabry-Pérot cavities by gray scale nanolithography. With controlled hydrogenation and dehydrogenation, magnesium undergoes unique metal and dielectric transitions, enabling distinct blank and color states from the pixelated Fabry-Pérot resonators. Following such a scheme, we first demonstrate dynamic Ishihara plates, in which the encrypted images can only be read out using hydrogen as information decoding key. We also demonstrate a new type of dynamic color generation, which enables fascinating transformations between black/white printing and color printing with fine tonal tuning. Our work will find wide-ranging applications in full-color printing and displays, colorimetric sensing, information encryption and anticounterfeiting.
Gesehen am 02.07.2018
Published online 19 July 2017